Advances in experimental optic nerve regeneration. Issue 6 (November 2017) - Chun, Bo Young; Cestari, Dean M.
Abstract : Purpose of review: Recent advances in experimental studies of optic nerve regeneration to better understand the pathophysiology of axon regrowth and provide insights into the future treatment of numerous optic neuropathies. Recent findings: The optic nerve is part of the central nervous system and cannot regenerate if injured. There are several steps that regenerating axons of retinal ganglion cells (RGCs) must take following optic nerve injury that include: maximizing the intrinsic growth capacity of RGCs, overcoming the extrinsic growth-inhibitory environment of the optic nerve, and optimizing the reinnervation of regenerated axons to their targets in the brain. Recently, some degree of experimental optic nerve regeneration has been achieved by factors associated with inducing intraocular inflammation, providing exogenous neurotrophic factors, reactivating intrinsic growth capacity of mature RGCs, or by modifying the extrinsic growth-inhibitory environment of the optic nerve. In some experiments, regenerating axons have been shown to reinnervate their central targets in the brain. Summary: Further approaches to the combination of aforementioned treatments will be necessary to develop future therapeutic strategy to promote ultimate regeneration of the optic nerve and functional vision recovery after optic nerve injury.